Synergetic effects of tank background and food colouration on feeding preferences of seahorse Hippocampus barbouri - Ismail, Syahira; Christianus, Annie; Chen, Cheng-Ann; Kawamura, Gunzo; Lim, Leong-Seng; Abd Halid, Nur Fatihah (Springer, 2023)
Predator colour preference enables the recognition of prey items, and can be useful when designing potential feed. However, the preferred food colour varies depending on the surrounding background colour and light intensity. This study aimed to determine whether the food colour can increase the preference for non-live food, as seahorses prefer live food. Food colour preferences were determined by observing the first response (approach and ingestion) of a sub-adult Hippocampus barbouri, using different background colours. Seahorses (SL: 7.56 ± 0.35 cm and WW: 0.58 ± 0.10 g) were reared in tanks with red, blue and green backgrounds. Sergestid shrimp Acetes sibogae (TL: 1.00 ± 0.05 cm), were used as the tested food, dyed blue, green, red or yellow, while non-dyed shrimp were used as a control. During the trial, shrimp of two different colours were presented against three different backgrounds within the seahorse’s visual field. The frequency of the first response was recorded, and a quantitative analysis was made using a chi-square of independence test and Thurstone’s law of comparative judgment. Against all backgrounds, the first response was significantly biased toward non-dyed shrimp. Yellow- and green-dyed shrimp were also significantly preferred against green and red backgrounds, respectively. Thus, this study demonstrated that sub-adult H. barbouri has colour preferences. However, further study is required to confirm colour vision in H. barbouri.